The Effect of Competency, Motivation of Work Training on the Work Achievement of Employees Classification Indonesia Bureau of Batam Branch - Sri Yanti; Rusdin Haluddin; Jemmy Rumengan; Maniah Maniah (INOBIS: Jurnal Inovasi Bisnis dan Manajemen Indonesia, 2020)
In this study, the aim of this research is to determine the effect of competence on the work performance of employees of the Batam branch of the Indonesian classification Bureau, to determine the effect of motivation on employee performance of the Batam branch of the Indonesian classification bureau, to determine the effect of training on employee performance at the Batam branch of the Indonesian classification Bureau, to determine the effect of competence , Motivation and training on employee work performance of the Batam branch of the Indonesian classification bureau. The sample of the study amounted to 36 people, this study obtained the results Y = 7.582+ 0.036x1 + 0.414x2 + 0.293x3 + e. With a R2 value of 0.625 (62.5%). The competency variable has a positive and insignificant effect on work performance of 0.036, a significant level of 0.829 is greater than 0.05, the hypothesis Ho is rejected and Ha is accepted, the conclusion of the hypothesis is rejected, motivation has a significant effect on work performance by 0.414, the significant level is 0.001 less than 0.05. , the hypothesis Ha is accepted and Ho is rejected, the conclusion of the hypothesis is accepted. Training has a significant effect on work performance of 0.293 with a significant level of 0.033 smaller than 0.05 hypothesis Ha is accepted and Ho is rejected, the conclusion of the hypothesis is accepted. Competence, motivation and training have an effect on employee work performance. Simultaneous Test (F test) is 17.809 with a significant value of 0.000 where the value is less than 0.05. The hypothesis Ho is rejected and Ha is accepted.